Hepatoprotective activities of rosmarinic acid against extrahepatic cholestasis in rats. (October 2017) - Lin, Shih-Yi; Wang, Ya-Yu; Chen, Wen-Ying; Liao, Su-Lan; Chou, Su-Tze; Yang, Ching-Ping; Chen, Chun-Jung
Abstract: Though rosmarinic acid possesses nutritional, pharmaceutical, and toxic properties and shows therapeutic potential on liver diseases, its therapeutic effects against cholestatic liver diseases have not been proven. Using an extrahepatic cholestasis rat model by bile-duct ligation (BDL), daily oral administration of rosmarinic acid showed improvement effects on liver histology, serum biochemicals, ductular reaction, oxidative stress, inflammation, and fibrosis. Rosmarinic acid alleviated BDL-induced transforming growth factor beta-1 (TGF-β1) production and hepatic collagen deposition, and the anti-fibrotic effects were accompanied by reductions in matrix-producing cells and Smad2/3. BDL rats showed increased hepatic NF-κB/AP-1 activities, inflammatory cell infiltration/accumulation, and cytokine production, and these signs of hepatic inflammation were ameliorated by rosmarinic acid. Mechanistic study revealed an inhibitory effect of rosmarinic acid on the axis of the high mobility group box-1 (HMGB1)/toll-like receptor-4 (TLR4) in BDL rats. Results of cultured hepatic stellate cells further showed the impacts of rosmarinic acid which attenuated TGF-β1-induced stellate cell mitogenic and fibrogenic activation. Our findings support the concept that rosmarinic acid could serve as a hepatoprotective agent, and dietary rosmarinic acid supplementation may be beneficial in terms of improving cholestasis-related liver injury via mechanisms involving resolution of oxidative burden and down-regulation of HMGB1/TLR4, NF-κB, AP-1, and TGF-β1/Smad signaling. Graphical abstract: Highlights: Bile duct ligation caused extrahepatic cholestasis in rodents. Rosmarinic acid showed improvement effects against cholestasis. Rosmarinic acid attenuated hepatic TGF-β1 signaling in BDL rats. Rosmarinic acid attenuated hepatic NF-κB/AP-1 activities in BDL rats. Rosmarinic acid attenuated hepatic HMGB1/TLR4 signaling in BDL rats.